Analisis Kepuasaan Pelanggan Labbaik Chicken Menggunakan CSI (Customer Satisfaction Indek) - Resti Apipah; Khoirunnida; Syamsul Hidayat (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2024)
This research aims to determine the level of customer satisfaction with the products and services provided by the Labbaik Chicken Company. The method used was a survey using an instrument in the form of a questionnaire which was delivered to a research sample of 330 respondents. Data was analyzed using the Customer Satisfaction Index (CSI) to measure the overall level of customer satisfaction. The research results showed that the CSI value obtained was 54.19 which was in the "Quite Satisfying" category. This indicates that in general Labbaik Chicken customers are quite satisfied with the products and services they receive. Factors that have a positive influence on customer satisfaction are food quality, taste and speed of service. Meanwhile, prices were seen as quite expensive by some respondents. This research is expected to provide an overview of the level of satisfaction of Labbaik Chicken customers and input for improving service quality in order to increase customer loyalty in the future.